Patient Information Needs During Ambulatory Medication Changes: A Qualitative Study - Elaine Giletta; Vanessa B. Hurley; Yushi Yang; Jessica L. Schwartz; Rabia Jalalzai; Nicole L. Mollenkopf; Raquel Mayne; Samantha I. Pitts (Journal of Patient-Centered Research and Reviews, 2025)
Purpose: We performed interviews with patients and caregivers to explore whole-person, whole-regimen information needs at times of routine outpatient medication changes. We categorized information needs in this relatively unstudied context and identified which needs were commonly recognized as insufficiently met.